UPAYA HUKUM KEBERATAN TERHADAP SURAT KETETAPAN PAJAK DAERAH - BRYANANTA BAYU SAPUTRA, S.H., 031514253007 (2017)
Development in all areas within the city requires financing originating from local revenues, especially those sourced from local taxes, which aims to minimize the role of sources of finance, either from the central government or from foreign loans. In connection with the implementation of Article 83 from Mojokerto Regional Regulation No. 12/2010, this is contradictory to the provision of Article 103 Clause 4 from Act 28/2009 regarding Regional Taxes & Levies, which will inevitably lead to Conflict Norma incriminating taxpayers, and in the future This conflict of norms will cause obstacles in the collection of Local Taxes. This research uses normative juridical research type with statute approach and conceptual approach. The result of this study, the ratio legis is to provide preventive law protection against taxpayers of the conflict of norms arising from Article 83 from Mojokerto Regional Regulation No. 12/2010 is an objection may be filed if the taxpayer has paid at least 50% of tax payable, of course Burdensome taxpayers who are not able to pay taxes and contrary to Article 103 Clause 4 of Act No. 28/2009. Should immediately be revised Mojokerto Regional Regulation No. 12/2010 to avoid conflict of norms that occur.